Sustainable management of the coastal water pH of Pulau Tuba using the Inverse Distance Weighted (IDW) method / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Abd.Aziz, Khairul Naim; Roslani, Muhammad Akmal; Zainol, Zamzila Erdawati (Universiti Teknologi MARA, Perlis, 2021)
Ocean acidification can be managed and monitored effectively through the application of spatial interpolation methods. The purpose of this study is to evaluate the precision of the Inverse Distance Weighted (IDW) interpolation method to estimate and map the coastal water pH for the sustainability of Pulau Tuba, Langkawi, Kedah. About 30 sampling points have been set up during two sampling activities in November 2018. The pH meter has been calibrated and lowered to 1 meter below the water surface to measure the reading of pH. The development of the spatial model was developed using the spatial analyst tool available in ArcGIS Software. Several types of statistical analyses were carried out to compare the observed and predicted value of pH. such as correlation analysis, regression analysis, and error analysis. Accuracy assessment was conducted later after the transformation of a spatial model into a surface map. The study found that the IDW interpolation method successfully interpolated the pH readings. The result showed that there is a strong positive correlation between the observed and predicted values. For error analysis, Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) were recorded at 0.033 and 0.044, respectively. After the transformation of the spatial model to the surface map, the accuracy of the map is recorded at 81.25%. The study also outlines the sustainable mechanisms and opportunities for the government to implement in combatting the ocean acidification processes. The map produced can be used for social and economic development and the protection of biodiversity for the coastal water of Pulau Tuba.